Identifying sustainability readiness for Industry 5.0: a cultural perspective from developing country - Tanjung, Tia; Ghazali, Ihwan; Md Yasir, Ahmad Shah Hizam; Wan Mahmood, Wan Hasrulnizzam; Herawan, Safarudin Gazali (Frontiers in Sustainability, 2026)
The shift from Industry 4.0 toward the human-oriented and sustainability-driven Industry 5.0 marks a significant transformation in industrial priorities. This research explores how Malaysian organizations, particularly in the manufacturing and logistics sectors, are preparing for sustainable development within this new industrial context. Emphasizing the impact of cultural attributes on organizational readiness, a quantitative survey was conducted involving 150 participants from company in Malaysia. The results demonstrate that culturally embedded factors such as leadership styles, workforce mindset, and openness to technological advancement strongly influence the adoption of sustainable approaches. Among these, leadership engagement and people-centered innovation are identified as crucial enablers. The study provides a localized understanding of how sustainability initiatives can be more effectively aligned with Industry 5.0 objectives when cultural dynamics are taken into account. These insights are valuable for both policymakers and practitioners seeking to foster sustainable transformation within culturally diverse industrial settings.